Epidemiological analysis of skin cancer in Brazil - Mariana Dultra; Stefanie Gallotti; José R. Pegas (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Background: Skin cancer is divided into melanoma or non-melanoma skin cancer. Non-melanoma skin cancer is the most common type of cancer in humans. Melanoma, on the other hand, has a low incidence, but high lethality. In view of the great European miscegenation and great sun exposure in Brazil, it is of great value to study the epidemiology of skin cancers, to determine the magnitude of this disease in society. Objectives and methods: This study determines skin cancer indicators in Brazil, by place of residence, in the federal units and regions of Brazil, between 2015 and 2021. Conclusion: The values evaluated allow us to conclude that skin cancer is still a disease that causes significant morbidity in Brazil, despite the primary and secondary prevention measures established.